Postcolonial transitional justice: Zimbabwe and beyond - Moyo, Khanyisela (Transitional justice, 2019)
Introduction -- Basic concepts of the study and a postcolonial critique -- Rule of law and judicial independence -- Land reform and transitional justice -- Minorities in postcolonial transitions -- Dealing with the legacy of impunity -- Conclusion.